Peers and Culture - María Sáez-Martí; Anna Sjögren (The Research Institute of Industrial Economics (IUI), 2005)
We analyze the evolution of cultural traits when parents purposefully invest resources in order to socialize their children to the cultural traits that maximize child lifetime utility. We assume that children are not passive in their adoption of traits from peers. Instead they are guided by an evaluation of the merit of traits. We show that such evaluation is likely to render this process of oblique transmission biased. We then show that when transmission of traits from society is biased or frequency dependent, cultural diversity is sustainable even when all parents strive to transmit the same trait. We also show that demand for cultural pluralism on the part of parent does not guarantee cultural diversity.
Keywords: D10; I20; J13; 330; Peer Groups; Cultural Transmission; Cultural Diversity; Oblique Transmission; Kinder; Bildung; Soziale Integration; Eltern; Soziale Gruppe